Precision Structural Interpretation of Site-Specific N-Glycans in Seminal Plasma - Xin, Miaomiao; Xu, Yintai; You, Shanshan; Li, Cheng; Zhu, Bojing; Shen, Jiechen; Chen, Zexuan; Shi, Wenhao; Xue, Xia; Shi, Juanzi; Sun, Shisheng (Journal of proteome research, 2022)
N-Linked glycoproteins are rich in seminal plasma, playing various essential roles in supporting sperm function and the fertilization process. However, the detailed information on these glycoproteins, particularly site-specific glycan structures, is still limited. In this study, a precision site-specific N-glycoproteome map of human seminal plasma was established by employing the site-specific glycoproteomic approach and a recently developed glycan structure interpretation software, StrucGP. A total of 9567 unique glycopeptides identified in human seminal plasma were composed of 773 N-linked glycan structures and 1019 N-glycosites from 620 glycoproteins. These glycans were comprised of four types of core structures and 13 branch structures. The majority of identified glycoproteins functioned in response to stimulus and immunity. As we reported in human spermatozoa, heavy fucosylation (fucose residues ≥6 per glycan) was also detected on seminal plasma glycoproteins such as clusterin and galectin-3-binding protein, which were involved in the immune response of biological processes and reactome pathways. Comparison of site-specific glycans between seminal plasma and spermatozoa revealed more complicated glycan structures in seminal plasma than in spermatozoa, even on their shared glycoproteins. These present data will be greatly beneficial for the in-depth structural and functional study of glycosylation in the male reproduction system.
Keywords: glykoproteiny; glykopeptidy; polysacharidy; Glycopeptides; lidé; mužské pohlaví; Male; Glycoproteins; Polysaccharides; Glycosylation; glykosylace; Semen; sperma; Humans